Manajemen Pembelajaran Tahfidzul Qur’an Santri di Boarding School - Dinda Azzahra; Sendi Nurtanti; Lail Syageta Lifeaningrum; Anaas Tri Ridlo Dina Yuliana; Fadhlurrahman Fadhlurrahman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explain how the tahfidz program at Boarding School Muhammadiyah 1 Wates is managed. Memorizing the Qur'an is an important tradition in Islam that continues to be maintained through educational institutions such as Islamic boarding schools. The tahfidz program at Boarding School Muhammadiyah 1 Wates is designed to increase students' interest and ability in memorizing the Qur'an, but its success requires planned and structured management. This program is one of the best programs and has full support from the school as the parent manager of the Boarding School. In fostering students' interest in memorizing the Qur'an at the Muhammadiyah 1 Wates Boarding School, it includes planning, implementation, evaluation, form of methods and supporting and inhibiting factors of the tahfidz program in increasing interest in memorizing the Qur'an. The research uses a descriptive qualitative method and is collected using interview, observation and documentation instruments. The results of the study show that in managing a special program in increasing interest in Qur'an memorization at Boarding School Muhammadiyah 1 Wates, starting from the planning, implementation, evaluation, and types of methods, as well as supporting and inhibiting elements of the class tahfidz program which are intended to increase interest in Qur'an memorization. The research shows that the management of the special class tahfidz program at the Muhammadiyah 1 Wates Boarding School is running well in terms of planning, organizing, implementing, and evaluating. The methods used in the implementation of this special class tahfidz program are the Tikror method (Repetition of reading 5-20 times in each block) and the Tasmi' method (Listening to verses that are read repeatedly). Supporting factors include a comfortable place for students, support from parents, teachers, and administrators of the tahfidz program, as well as health factors and a desire to learn. Inhibiting factors include indiscipline in managing time, limited knowledge, student disobedience, interpersonal problems, speed of forgetting memorization, and laziness. The result of efforts to increase students' interest in memorizing the Qur'an is an increase in the number of people enrolled in special classes, the number of children who pass to take tasmi' bil goib per 1 Juz and students in special classes on average have reached their memorization targets.